2013
DOI: 10.31285/agro.17.481
|View full text |Cite
|
Sign up to set email alerts
|

Eficiencia energética en sistemas lecheros del Uruguay

Abstract: Reducir el consumo de energía fósil y aumentar la eficiencia energética de los predios agropecuarios resulta en ventajas ambientales y económicas. El objetivo de este trabajo fue analizar sistemas de producción de leche desde el punto de vista energético, para identificar las principales variables que inciden en la eficiencia energética y consumo de energía fósil, a través de un modelo de entradas y salidas. El modelo incluyó como entradas los costos energéticos de alimentos, mano de obra, electricidad, agroqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Hence, ranches with a higher degree of intensification of grazing cattle tend to be more energy efficient (LLANOS et al, 2018). Results of the energy efficiency of this study (Table 3) were lower than previously reported by LLANOS et al (2013). This author stratified energy efficiency in a dairy production system in the south of Uruguay as follows: low (1.40), medium (0.90), and high (0.86) productivities, respectively.…”
Section: Energy Efficiency and Productivity In Agro-ecosystemsmentioning
confidence: 40%
“…Hence, ranches with a higher degree of intensification of grazing cattle tend to be more energy efficient (LLANOS et al, 2018). Results of the energy efficiency of this study (Table 3) were lower than previously reported by LLANOS et al (2013). This author stratified energy efficiency in a dairy production system in the south of Uruguay as follows: low (1.40), medium (0.90), and high (0.86) productivities, respectively.…”
Section: Energy Efficiency and Productivity In Agro-ecosystemsmentioning
confidence: 40%
“…Los resultados obtenidos mostraron valores de eficiencia inferiores a los relatados por Llanos et al (2013) para lecherías de Uruguay, aunque coinciden con los obtenidos por Tieri et al (2017), en la cuenca central de Argentina. Las diferencias entre las experiencias pueden relativizarse por causa de los enfoques adoptados y los límites impuestos al análisis energético.…”
Section: Discussionunclassified